Phenomenology Of Bullying In Islamic Boarding School From A Youth Development Perspective - Lucky Damara Yusuf; Shohibul Ulum (Penerbit Presisi Pustaka, 2026)
This research is a naturalistic-qualitative research using a social phenomenology approach. The data source is the students of the Islamic Boarding School. Data were collected through participant observation, interview, documentation, and focus group discussion (FGD) methods. Based on the research results, it can be concluded that. The factors causing bullying behavior at Islamic Boarding Schools are influenced by two main factors, namely the social environment, and the social climate of the boarding school. The environment at the Islamic boarding school where students interact socially, play and develop often results in quarrels. Playmates who often commit acts of violence against others will have an impact on the child's development.